Teaching animal hygiene in the University of Ibadan, Nigeria (2003)
Animal hygiene is taught under the title veterinary public health and preventive medicine in the University of Ibadan, Ibadan, Nigeria. The term animal hygiene is not commonly used here, but the definition of animal hygiene cogently interprets the composition and integration of the ten subject areas taught under veterinary public health and preventive medicine in Ibadan. There are three units within the department, namely; veterinary public health, veterinary preventive medicine, and wildlife and fish ecology and diseases. The essential pursuit of each of these three units is animal hygiene in the order of the subdivisions into veterinary preventive medicine, food safety and environmental protection basics of the animal and human health